2015
DOI: 10.1039/c5cc02009c
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, structure, and versatile reactivity of pseudocyclic benziodoxole triflate, new hypervalent iodine reagent

Abstract: A new pseudocyclic triflate derivative of benziodoxole (IBA-OTf) was prepared and characterized by X-ray analysis. This highly electrophilic reagent readily reacts with various organic substrates to give the corresponding products in good yields. Furthermore, IBA-OTf can be used as a catalyst with m-chloroperoxybenzoic acid as the terminal oxidant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
63
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 67 publications
(66 citation statements)
references
References 67 publications
2
63
0
1
Order By: Relevance
“…© ARKAT USA, Inc Recently, the catalytic hypervalent iodine-mediated oxidative cyclization reactions of aldoximes with nitriles have been reported. 34,64 This process also involves the hydroxy(aryl)iodonium species generated in situ from 2-iodobenzoic acid, m-CPBA and trifluoromethanesulfonic acid as confirmed by Scheme 22. Preparation of oxadiazoles from aldoximes with nitriles using catalytic hypervalent iodine species.…”
Section: Oxidative Cyclization Of Aldoximes Using Catalytic Hypervalementioning
confidence: 99%
See 2 more Smart Citations
“…© ARKAT USA, Inc Recently, the catalytic hypervalent iodine-mediated oxidative cyclization reactions of aldoximes with nitriles have been reported. 34,64 This process also involves the hydroxy(aryl)iodonium species generated in situ from 2-iodobenzoic acid, m-CPBA and trifluoromethanesulfonic acid as confirmed by Scheme 22. Preparation of oxadiazoles from aldoximes with nitriles using catalytic hypervalent iodine species.…”
Section: Oxidative Cyclization Of Aldoximes Using Catalytic Hypervalementioning
confidence: 99%
“…3,6,[84][85][86] Recently the first examples of iodine(III) catalyzed oxidative cycloaddition reactions of aldoximes have been reported. [32][33][34]64,87,88 In 2013, our group was the first to report the hypervalent iodineinduced catalytic cyclization of aldoximes. 32 We have found that oxidative heterocyclization of various aldoximes 65 with alkenes 66 or alkynes 67 in the presence of catalytic aryl iodide and Oxone as the oxidant affords the corresponding isoxazolines 68 or isoxazoles 69 in moderate to good yields (Scheme 20).…”
Section: Oxidative Cyclization Of Aldoximes Using Catalytic Hypervalementioning
confidence: 99%
See 1 more Smart Citation
“…[7b,c] We have recently reported a novel hypervalent iodine reagent, IBA-OTf, which was prepared from 2-iodosylbenzoic acid and trifluorometh-A C H T U N G T R E N N U N G anesulfonic acid and could be used as a stoichiometric oxidant for the oxidative cyclization of aldoximes with nitriles. [8] However, to the best of our knowledge, the cyclization reaction of aldoximes with maleimides using hypervalent iodine(III) compounds has not been previously reported.…”
mentioning
confidence: 97%
“…Oximes have been utilized in the synthesis of nitrile oxides 2,3 to afford a variety of cycloadducts such as isoxazolines, 4 isoxazoles 5 and oxadiazoles. 6 Metal-catalyzed rearrangements of oxime-containing molecules have also yielded biologically relevant structures, such as oxazepines, 7 pyridols, 8 pyridines, 9 and pyrroles. 10 …”
mentioning
confidence: 99%